Rare horizontal transmission does not hide long-term inheritance of SINE highly conserved domains in the metazoan evolution. Issue 6 (11th September 2016) - Luchetti, Andrea; Mantovani, Barbara
Abstract : Transposable elements (TEs) are self-replicating, mobile DNA sequences which constitute a significant fraction of eukaryotic genomes. They are generally considered selfish DNA, as their replication and random insertion may have deleterious effects on genome functionalities, although some beneficial effects and evolutionary potential have been recognized. Short interspersed elements (SINEs) are non-autonomous TEs with a modular structure: a small RNA-related head, a body, and a long interspersed element-related tail. Despite their high turnover rate and de novo emergence, the body may retain highly conserved domains (HCDs) shared among divergent SINE families: in metazoans, at least nine HCD-SINEs have been recognized. Data mining on public molecular databases allowed the retrieval of 16 new HCD-SINE families from cnidarian, molluscs, arthropods, and vertebrates. Tracking the ancestry of HCDs on the metazoan phylogeny revealed that some of them date back to the Radiata–Bilateria split. Moreover, phylogenetic and age versus divergence analyses of the most ancient HCDs suggested that long-term vertical inheritance is the rule, with few horizontal transfer events. We suggest that the evolutionary conservation of HCDs may be linked to their potential to serve as recombination hotspots. This indirectly affects host genomes by maintaining active and diverse SINE lineages, whose insertions may impact (either positively or negatively) on the evolution of the genome.